THE POTENTIAL OF MICRO-CHINESE MEDICINE OSMOTHERAPY USING NANOPARTICLES AS A TREATMENT FOR CHRONIC KIDNEY DISEASE - Alvionita Thana; Fernando Corneles Moniharapon; Kristin Armis Pasaribu; Sindy Friska; Wahyu Irawati (Universitas Medan Area, 2022)
The kidneys are the most important to excretory organs because they have function to remove waste products from the body has metabolism. In the excretory system, the damage that could occur is the kidney has decreased until finally unable to perform its function properly which is called Chronic Kidney Disease (CKD). Chronic Kidney Disease caused by age, gender, and a history of diseases such as diabetes. One of the nanoparticle therapies that could be given to patients with chronic kidney disease is Micro-Chinese Medicine Osmotherapy. The purpose of this paper is to determine: 1) structure and how they work of the kidney and its relation to the urinary system, 2) causes and effects of chronic kidney disease on the urinary system, 3) mechanism of the urinary system in conditions of chronic kidney disease, and 4) mechanism and results of Micro-Chinese Medicine Osmotherapy. The research method used is a literature review from various sources which helps in reviewing the four focus of the study. Kidney is divided into three major parts, namely cortex, medulla, and renal pelvis. The excretory system has three stages, including filtration, reabsorption, and augmentation. Chronic kidney disease can be caused by age, where older age has a risk of developing CKD. Kidney disease can be divided into several stages, including normal, at risk of damage, kidneys are damaged, kidneys are not functioning properly and kidneys are no longer functioning or chronic kidney disease (CKD). The mechanism of action of Micro-Chinese Medicine Osmotherapy is divided based on its function, named as anti-inflammatory, anti-coagulation, and degradation. The results of treatment for kidney disease is Micro Medicine Osmotherapy could make all renal arteries of patients with chronic kidney disease widen and increase perfusion.